Pertanggungjawaban Korporasi Berdasarkan Kesalahan Menurut Hukum Pidana - Satwika Narendra; Gde Made Swardhana; Diah Ratna Sari Hariyanto (CV. ULIL ALBAB CORP, 2024)
This research aims to analyze the legal construction that the actions of administrators (other people) can be declared as unlawful corporate acts (according to criminal law), as well as to identify judges' decisions (jurisprudence) that provide criminal sanctions to corporations and place corporations as subjects of criminal acts. The research method “used is normative legal research method with the approach used includes statutory approach and conceptual approach”. The results showed that (1) The legal construction that the actions of the management (other people) can be declared as unlawful corporate acts (according to criminal law) is supported by the theory of strict liability, vicarious liability, direct corporate criminal liability, aggregation theory and corporate culture model. (2) The legal construction that corporate actors can be declared to have fault and therefore be held accountable under criminal law shows that intent or negligence or negligence is found in the people who are tools of the corporation. The fault is not individual but collective. The corporation still has fault that is constructed as the fault of the management or members of the board of directors. So, the corporation can still have a mistake with the construction of the mistake of the management or members of the board of directors; and (3) Criminal witnesses include imprisonment, punishment by paying compensation jointly, fines, and paying compensation. However, there are punishments imposed on corporations by the Court of First Instance, but they were overturned by the Supreme Court.